EL GRUPO DE VISEGRADO – DEL EURO-IDEALISMO AL PRAGMATISMO - Ivanova , Diana (Revista Inclusiones, 2018)
The purpose of this article is to present the evolution in the attitude of the Visegrad Group to European Union (EU) from Euro-idealism towards pragmatism. It will be realized through the implementation of basic tasks - revealing the impact of soviet perestroika on political processes in Poland, Hungary and Czechoslovakia at the end of the 1980s; clarifying the factors that influenced the creation of the organization in the process of European integration of its members; analysis of the documents adopted at its forums, and the views of leading politicians from the Visegrad states. The analysis of the relations between the EU and the states of the Visegrad Group allows to conclude that the Euro-idealism that is characteristic of the period prior to Visegrad countries adoption in the EU is completely understandable after the four decades of one-party rule. Gradually, however, after passing the initial euphoria of EU membership, the Euro-idealism goes into pragmatism, the core of which is the desire to defend national interests.